Rancang Bangun Sistem Pemantauan dan Kendali Budidaya Anggur Dengan Penerapan Internet Of Things (IoT) Berbasis Android - Nur Fitriana Putri; Rahmi Hidayati; Irma Nirmala (JURIKOM (Jurnal Riset Komputer), 2023)
Grape vines are plants that can grow well in lowland areas, especially coastal areas. The very hot weather climate is an inhibiting factor in the growth of grape vines. So it is necessary to help greenhouse media technology with the application of the Internet of Things (IoT) to create the desired conditions in an effort to protect plants as well as temperature and humidity conditions that can attack grape plants, adjusting the parameters needed. Vine testing parameters include air temperature, air humidity and soil moisture. In the system that has been created, the system will monitor the conditions of air temperature, air humidity and soil moisture. In addition, the system will manually and automatically control the fan, mist maker and pump according to predetermined values. The results of the sensor test show an accuracy for air temperature of 95.36%. The result of the test for air humidity is 88.67%. The result of the capacitive soil moisture sensor test for soil moisture is 99.85%.